Drugs for the prevention and treatment of COVID-19 and its complications: An update on what we learned in the past 2 years - Remuzzi, Giuseppe; Schiaffino, Stefano; Santoro, Maria Gabriella; FitzGerald, Garret A.; Melino, Gennaro; Patrono, Carlo (Frontiers in Pharmacology, 2022)
The COVID-19 Committee of the Lincei Academy has reviewed the scientific evidence supporting the efficacy and safety of existing and new drugs/biologics for the preventing and treating of COVID-19 and its complications. This position paper reports what we have learned in the field in the past two years. The focus was on, but not limited to, drugs and neutralizing monoclonal antibodies, anti-SARS-CoV-2 agents, anti-inflammatory and immunomodulatory drugs, complement inhibitors and anticoagulant agents. We also discuss the risks/benefit of using cell therapies on COVID-19 patients. The report summarizes the available evidence, which supports recommendations from health authorities and panels of experts regarding some drugs and biologics, and highlights drugs that are not recommended, or drugs for which there is insufficient evidence to recommend for or against their use. We also address the issue of the safety of drugs used to treat underlying concomitant conditions in COVID-19 patients. The investigators did an enormous amount of work very quickly to understand better the nature and pathophysiology of COVID-19. This expedited the development and repurposing of safe and effective therapeutic interventions, saving an impressive number of lives in the community as well as in hospitals.